Absent Pulmonary Valve Syndrome with Non-Confluent Branches: Case Report and Literature Review - Tetyana Ye. Hura; Oleksandr S. Stychynskyi; Oleksandr V. Teterin; Raad Tammo (Ukrainian Journal of Cardiovascular Surgery, 2024)
Absent pulmonary valve syndrome (APVS) is a rare form of congenital heart defect. Among the various variations of this rare anomaly are non-confluent branches of the pulmonary artery (PA) with anomalous origin of one of the PA branches from the patent ductus arteriosus (PDA). Constriction of the PDA in early neonatal age may result in cessation of blood supply to one of the pulmonary artery branches, leading to exclusion of one lung from circulation and gas exchange processes. PDA stenting creates a reliable source of blood flow, and as a first step, an endovascular approach was chosen for treatment.Case report. A newborn (3 kg) with a prenatal diagnosis of APVS and a non-confluent left PA branch filling through PDA was chosen for PDA stenting. Considering the complex anatomy of the heart defect, it was decided to perform PDA stenting to delay total repair until the patient reaches optimal age and weight. Our patient successfully underwent PDA stenting as the first stage, which provided conditions for blood supply to one lung. The second stage involved total repair with good long-term results.Conclusion. APVS treatment may have several options of surgical correction, differing from each other depending on the anatomical features of the defect and the patient’s age. Palliative treatment options help the child transition from the neonatal period and gain optimal weight for total repair.. Analyzing the data from the presented literature, it is noted that prenatal diagnosis is an important stage in determining the urgency and choice of treatment tactics for this defect.